System crash driven by competition : a simulation study - Zhao, Mengjiao (Nanyang Technological University, 2020)
The world where we are living can be described as a complex world. Complex systems are systems that consist of many components and multiple hierarchies, in which those components collaborate to create a functioning whole. In a complex network system, the impact of a local hazard/fault/disturbance can quickly spread out to the whole system due to a domino effect, cascading effect, and/or ripple effect and eventually evolves into a large-scale disaster [1] [2]. In this project, I simulate some complex systems with different cascading models using the Python programing language. Extensive simulations are carried out to further investigate complex systems’ performance with different logic gates and conditions. Some real-world complex network cases are also discussed to show the consistency with the simulation results.